Consumer protection of users of nipah-sadu crossing transportation services in nipah panjang district, tanjung jabung east regency - Baso Iping (IHSA Institute, 2023)
The approach used is a normative juridical approach supported by an empirical juridical approach. The data used are primary data and secondary data. The data collection technique used is through a literature study/document study and interviews. The data obtained is presented in a qualitative descriptive form. The result of the research is that the rights and obligations of consumers of Nipah Panjang – Sadu ferry services are not in accordance with the regulations, for example there is no compensation, compensation and/or reimbursement in the event of an accident and tickets have not been provided as proof of the crossing transportation agreement. Likewise, the rights and obligations of business actors have not been implemented because there is no good faith from the business actors in carrying out their business activities, correct, clear and honest information has not been given regarding the conditions and guarantees of the goods and/or services used. There is no quality assurance. goods and/or services used.